A New Abnormality of Platelet Function - Bowie, E. J. Walter; Thompson, John H., Jr; Owen, Charles A, Jr (Thrombosis and Haemostasis, 1964)
This report concerns seven patients with thrombopathy, one of whom, a patient with a moderately severe bleeding tendency, exhibited a type of platelet deficiency not previously recorded. There was indirect evidence of platelet insufficiency in the prothrombin consumption test, which was not substantiated by direct examination of platelet function in the thromboplastin generation test. Since no antiplatelet activity could be demonstrated in the plasma, we are proposing the existence of a plasmatic factor which is necessary for the normal function of platelets, a factor lacking in this patient’s plasma.